Die norddeutsche Choralbearbeitung - rein funktionale Musik? - Belotti, Michael (Muzikološki zbornik, 2011)
Liturgical organ-playing depended largely on improvisation in the Baroque era. North German organ chorales were not primarily written for practical use but rather as examples of different compositional techniques for students, or testimonies of their composers' skills. Johann Sebastian Bach, who had copied and studied the large-scale chorale fantasias of Johann Adam Reinken and Dieterich Buxtehude in his early years, was able to improvise in the manner of the North German organists during his visit to Hamburg in 1720.
Keywords: alternatim practice; improvisational practice; improvizacijska praksa; North German organ music; organ chorale; orgelski koral; praksa alternatim; severnonemška orgelska glasba